Pharmacogenetics and Inflammatory Bowel Disease - Phillips, A. M.; Hare, N. C.; Satsangi, J. (Current Pharmacogenomics and Personalized Medicine, 2008)
The inflammatory bowel diseases, Crohn's disease and ulcerative colitis, are common causes of significant morbidity, especially in young people. Current knowledge of aetiology is incomplete, but increasingly the evidence points towards a combination of appropriate environmental triggers in a genetically susceptible individual. Therapeutic options include 5-aminosalicylates, corticosteroids and immunosuppressants such as azathioprine and 6-mercaptopurine. These treatments have widely accepted limitations, thus catalyzing the development of the newer biological agents, such as infliximab, which now has an established role in the induction and maintenance of remission of Crohn's disease and in the induction of remission of acute severe ulcerative colitis. Of the pharmacogenetic studies to date in inflammatory bowel disease, it is only the measurement of thiopurine methyltransferase (TPMT) levels before the induction of thiopurine treatment that has had any clinical impact. Although TPMT screening has relatively low sensitivity for identifying patients at risk of complications, it is clear that patients who are homozygous for TPMT alleles are at higher risk of myelosuppression when treated with thiopurines. In this article we review the current understanding of genetic polymorphisms associated with an increased risk of developing inflammatory bowel disease, genetic determinants of metabolism of the drugs used in the management of inflammatory bowel disease and discuss their influence on drug efficacy and the risk of developing side effects.
Keywords: thiopurine methyltransferase (TPMT)